Fenton: A Systematic Review of Its Application in Wastewater Treatment - Pimentel Prates, Matheus; de Oliveira Loures Marcionílio, Suzana Maria; Borges Machado, Karine; Medeiros de Araújo, Danyelle [UNESP]; Martínez-Huitle, Carlos A. [UNESP]; Leão Arantes, Arizeu Luiz; Ferreira da Silva Gadêlha, José Eduardo (My University, 2023)
The use of new technologies for the removal of pollutants from wastewater has become globally necessary due to the complexity and facilities defined by conventional treatments. Advanced oxidative processes, specifically the Fenton process, have become widely applied given their low cost and ease of use. Therefore, this study aimed to evaluate the progression of the scientific publications on the implementation of Fenton process, investigating their space–time evolution. Additionally, useful solutions, trends, and gaps in the applications for the removal of pollutants with this methodology were identified, and also different remediation strategies and the design of new treatments for wastewaters were identified within this scientometric analysis. Bibliometric research was conducted in two scientific databases, Web of Science and Scopus, from 2011 to 2022, and we identified 932 and 1263 studies with the word “Fenton,” respectively. When these publications are associated with the treatment of alternative effluents, an increase in publications from 2011 (r = 0.95, p < 0.001) and 2013 (r = 0.93, p < 0.001) was observed when analyzing both databases, indicating the relevance of the theme. Among these studies, several of them were conducted on the bench scale (89.8% and 98.3%, Web of Science and Scopus, respectively) and in aqueous matrix (97.8% and 98.4%, Web of Science and Scopus, respectively), with being China the main country with publications associated with these words (28.33% and 41.9%), while Brazil is related to 3.65% and 2.29% of the total studies in Web of Science and Scopus, respectively. In addition, this review provides a guideline for new applications for different species in the matrices and describes the evolution of technological solutions to meet Sustainable Development Goal 6: clean water and sanitation.
Keywords: advanced oxidative processes; pollution; scientometrics; wastewater